1996
DOI: 10.1126/science.272.5266.1310
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Abundant Ethane and Methane, Along with Carbon Monoxide and Water, in Comet C/1996 B2 Hyakutake: Evidence for Interstellar Origin

Abstract: The saturated hydrocarbons ethane (C2H6) and methane (CH4) along with carbon monoxide (CO) and water (H2O) were detected in comet C/1996 B2 Hyakutake with the use of high-resolution infrared spectroscopy at the NASA Infrared Telescope Facility on Mauna Kea, Hawaii. The inferred production rates of molecular gases from the icy, cometary nucleus (in molecules per second) are 6.4 X 10(26) for C2H6, 1.2 X 10(27) for CH4, 9.8 X 10(27) for CO, and 1.7 X 10(29) for H2O. An abundance of C2H6 comparable to that of CH4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
188
1
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 308 publications
(194 citation statements)
references
References 33 publications
3
188
1
2
Order By: Relevance
“…Our calculations assume that the Einstein A values for the lines in this band are identical to the Einstein A values for the lines in the ν 2 + ν 3 band, an assumption that was used previously by Mumma et al (1996) in their analysis of the H 2 O lines they observed in Comet Hyakutake (1996 B2) and which gave production rates that were comparable to those derived using other techniques (e.g., observations of OH). A recent ab initio calculation of the intensities of H 2 O lines (Partridge and Schwenke 1997) also gives excellent agreement (within 2%) with our estimate for the strength of the 2 02 − 3 03 line.…”
Section: H 2 Omentioning
confidence: 57%
See 3 more Smart Citations
“…Our calculations assume that the Einstein A values for the lines in this band are identical to the Einstein A values for the lines in the ν 2 + ν 3 band, an assumption that was used previously by Mumma et al (1996) in their analysis of the H 2 O lines they observed in Comet Hyakutake (1996 B2) and which gave production rates that were comparable to those derived using other techniques (e.g., observations of OH). A recent ab initio calculation of the intensities of H 2 O lines (Partridge and Schwenke 1997) also gives excellent agreement (within 2%) with our estimate for the strength of the 2 02 − 3 03 line.…”
Section: H 2 Omentioning
confidence: 57%
“…For T rot = 100 K, the abundance ratio limit is ∼4-6%. Our limit on CO production in GZ is similar to the estimated abundance of CO in the nucleus of Comets 1P/Halley (3.5%, Eberhardt 1998), Bradfield (C/1979 Y1) (3.5%, Feldman et al 1997), and Levy (C/1990 K1) (4.1-8.4%, Feldman et al 1997), and is significantly lower than the estimated CO abundances in comets Hyakutake (C/1996 B2) (∼14%, McPhate et al 1996; ∼20%, Biver et al 1999b;Mumma et al 1996 derived a preliminary value of 7%) and Hale-Bopp (∼10% at r ∼ 1 AU, according to Weaver et al 1999 andDiSanti et al 1999; ∼23% at r ∼ 1 AU, according to Biver et al 1999a). The CO abundance limit for GZ is somewhat larger than the abundance ratio observed in Comet Austin (C/1989 X1) (1.7%, Feldman et al 1997) and the upper limits derived for 103P/Hartley 2 (≤1.2%, Weaver et al 1994) and Shoemaker-Levy (C/1991 T2) (≤1.8%, Feldman et al 1997).…”
Section: Comentioning
confidence: 83%
See 2 more Smart Citations
“…If it occurred it would lead by hydrogenation to the presence of significant amounts of * C 2 H 6 , not currently detected. C 2 H 6 is seen in the cometry coma of comets Hyakutake and Hale-Bopp (Mumma et al 1996) and it is not known if this formed on the surface or in the gas phase. The bulk of surface reactions comprise routes to the complex molecules * CH 3 OH, * C 2 H 5 OH and * CH 3 OCH 3 .…”
Section: Reaction Setmentioning
confidence: 99%